2010
DOI: 10.1007/s12603-010-0135-5
|View full text |Cite
|
Sign up to set email alerts
|

The folic acid endophenotype and depression in an elderly population

Abstract: The potential influence of Cys-Gly on this phenotype is novel, and of considerable interest given that it has been linked to altered spontaneous activity and sedation in an animal model. Cys-Gly is a recognised ligand at the N-methyl-D-aspartatic acid (NMDA) subclass of glutamate receptor, a system associated with depression. In addition, the C677T-MTHFR association adds further support to existing findings underscoring the potential role of folate in depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…These findings suggest that cysteinylglycine may have a role in the pathophysiology of CVD and cancer. Recently, it was reported that cysteinylglycine was negatively associated with depression in an elderly population [39]. …”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that cysteinylglycine may have a role in the pathophysiology of CVD and cancer. Recently, it was reported that cysteinylglycine was negatively associated with depression in an elderly population [39]. …”
Section: Discussionmentioning
confidence: 99%
“…During the clinical assessment, all participants completed a face-to-face MMSE (41), selfcompleted a Hospital Anxiety and Depression Scale score (HADS) (42), and the neurologist obtained a brief medical history. Written informed consent for participation in this study, from participants that scored less than 24 on MMSE, was obtained by a registered proxy who was assessed as having the necessary cognitive capacity (41).…”
Section: Cognitive Testingmentioning
confidence: 99%
“…All participants completed estimation of daily intake of nutrients during an intervieweradministered validated food frequency questionnaire (FFQ), (23,42,43)…”
Section: Dietary Intake Of B-vitaminsmentioning
confidence: 99%
“…[20] The short form of the Arthritis Impact Measurement Scales 2 (AIMS2-SF) questionnaire was also used to evaluate health-related quality of life outcomes in individuals with arthritis as a tool which has been validated in individuals with arthritis and has been used other rheumatic conditions.. [21,22] Food Frequency Questionnaire All participants completed an estimation of daily nutrient intake during an intervieweradministrated validated food frequency questionnaire (FFQ). [23,24] The use of FFQ allowed for consideration of episodic consumption of food items consumed only a few times a year on special occasions such as a religious event, seasonal variations, and the overall variability of day-to-day diets. [25] The FFQ required participants to recall from a list of food items the type and quantity of food consumed over the past year.…”
Section: Measurementsmentioning
confidence: 99%